Proteomic profile of candida albicans biofilm - Abdulghani, Mazen; Iram, Rasiqua; Chidrawar, Priti; Bhosle, Kajal; Kazi, Rubina; Patil, Rajendra; Kharat, Kiran; Zore, Gajanan (Journal of Proteomics, 2022)
Candida albicans biofilms are characterized by structural and cellular heterogeneity that confers antifungal resistance and immune evasion. Despite this, biofilm formation remains poorly understood. In this study, we used proteomic analysis to understand biofilm formation in C. albicans related to morphophysiological and architectural features. LC-MS/MS analysis revealed that 64 proteins were significantly modulated, of which 31 were upregulated and 33 were downregulated. The results indicate that metabolism (25 proteins), gene expression (13 proteins), stress response (7 proteins), and cell wall (5 proteins) composition are modulated. The rate of oxidative phosphorylation (OxPhos) and biosynthesis of UDP-N-acetylglucosamine, vitamin B6, and thiamine increased, while the rate of methionine biosynthesis decreased. There was a significant modification of the cell wall architecture due to higher levels of Sun41, Pir1 and Csh1 and increased glycosylation of proteins. It was observed that C. albicans induces hyphal growth by upregulating the expression of genes involved in cAMP-PKA and MAPK pathways. This study is significant in that it suggests an increase in OxPhos and alteration of cell wall architecture that could be contributing to the recalcitrance of C. albicans cells growing in biofilms. Nevertheless, a deeper investigation is needed to explore it further.Significance: Candida sps is included in the list of pathogens with potential drug resistance threat due to the increased frequency especially colonization of medical devices, and tissues among the patients, in recent years. Significance of our study is that we are reporting traits like modulation in cell wall composition, amino acid and vitamin biosynthesis and importantly energy generation (OxPhos) etc. These traits could be conferring antifungal resistance, host immune evasion etc. and thus survival, in addition to facilitating biofilm formation. These findings are expected to prime the further studies on devising potent strategy against biofilm growth among the patients.
Keywords: Biofilm; Candida albicans; Cell wall; LC-MS; Metabolism; MS; proteomics

Opaque cell-specific proteome of Candida albicans ATCC 10231 - Abdulghani, Mazen; Telang, Saraswati; Desai, Manisha; Kadam, Shivdas; Kazi, Rubina; Shelar, Amruta; Patil, Rajendra; Maurya, Radheshyam; Zore, Gajanan (Medical Mycology, 2023)
Candida albicans, a polymorphic opportunistic pathogen of humans, can exist in different morphological forms like yeast, hyphae, pseudohyphae, chlamydospores, and white and opaque cells. Proteomic analysis of opaque form of C. albicans ATCC 10231 is carried out in the present study using microflow liquid chromatography-tandem mass spectrometry and validated using expression analysis of selected genes using reverse transcription quantitative real-time PCR and mitochondrial membrane potential assay. This is the first report identifying opaque cell-specific proteins of C. albicans. A total of 188 proteins were significantly modulated under opaque form compared to white cells, of which 110 were upregulated, and 78 were downregulated. It was observed that oxidative phosphorylation (OxPhos) and oxidative stress are enhanced in C. albicans cells growing under opaque form as proteins involved in OxPhos (Atp1, Atp3, Atp16, Atp7, Cox6, Nuc2, Qcr7, and Sdh12) and oxidative stress response (Gcs1, Gtt11, Gpx2, Sod1, Ccp1, and Lys7) were significantly upregulated. The maximum upregulation of 23.16- and 13.93-fold is observed in the cases of Ccp1 and Nuc2, respectively. The downregulation of proteins, namely Als1, Csh1, Sap9, and Rho1, determining cell surface chemistry indicates modulation in cell wall integrity and reduced adhesion of opaque cells compared to white cells. This study is significant as it is the first draft of the proteomic profile of opaque cells that suggests enhanced OxPhos, oxidative stress, and modulation in cell surface chemistry indicating reduced adhesion and cell wall integrity, which could be associated with reduced virulence in opaque form. However, a deeper investigation is needed to explore it further. Lay Summary Opaque form is one of the least studied morphological forms of Candida albicans. To the best of our knowledge, this is the first report providing opaque cell-specific proteome. It suggests enhanced oxidative phosphorylation, oxidative stress, and modulation in cell surface chemistry, which could be associated with reduced virulence in opaque form.
Keywords: albicans; C; LC-MS; MS; opaque; Oxidative stress; OxPhos; protein

Proteome dataset of Candida albicans (ATCC10231) opaque cell - Zore, Gajanan; Abdulghani, Mazen; Kodgire, Santosh; Kazi, Rubina; Shelar, Amruta; Patil, Rajendra (BMC Research Notes, 2024)
<h3 class="c-article__sub-heading" data-test="abstract-sub-heading" style="margin: 0px 0px 8px; box-sizing: inherit; font-size: 1.5rem; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, Oxygen-Sans, Ubuntu, Cantarell, "Helvetica Neue", sans-serif; line-height: 1.24; font-weight: 400;"> Objectives Candida albicans, a polymorphic yeast, is one of the most common, opportunistic fungal pathogens of humans. Among the different morphological forms, opaque form is one of the least-studied ones. This opaque phenotype is essential for mating and is also reported to be involved in colonizing the gastrointestinal tract. Considering the significance of the clinical and sexual reproduction of C. albicans, we have investigated the morphophysiological modulations in opaque form using a proteomic approach. <h3 class="c-article__sub-heading" data-test="abstract-sub-heading" style="margin: 24px 0px 8px; box-sizing: inherit; font-size: 1.5rem; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, Oxygen-Sans, Ubuntu, Cantarell, "Helvetica Neue", sans-serif; line-height: 1.24; font-weight: 400;"> Data description In the current investigation, we have used Micro-Liquid Chromatography-Mass Spectrometry (LC-MS/MS) analysis to create a protein profile for opaque-specific proteins. Whole-cell proteins from C. albicans (ATCC10231) cells that had been cultured for seven days on synthetic complete dextrose (SCD) medium in both as an opaque (test) and as a white (control) form cells were extracted, digested, and identified using LC-MS/MS. This information is meant to serve the scientific community and represents the proteome profile (SWATH Spectral Libraries) of C. albicans opaque form.